2020
DOI: 10.3390/nu12041008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age on Acute Appetite-Related Responses to Whey-Protein Drinks, Including Energy Intake, Gastric Emptying, Blood Glucose, and Plasma Gut Hormone Concentrations—A Randomized Controlled Trial

Abstract: Protein-rich supplements are used commonly to increase energy intake in undernourished older people. This study aimed to establish age effects on energy intake, appetite, gastric emptying, blood glucose, and gut hormones in response to protein-rich drinks. In a randomized double-blind, order, 13 older men (age: 75 ± 2 yrs, body mass index (BMI): 26 ± 1 kg/m2) and 13 younger (23 ± 1 yrs, 24 ± 1 kg/m2) men consumed (i) a control drink (~2 kcal) or drinks (450 mL) containing protein/fat/carbohydrate: (ii) 70 g/0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Basic features such as gender, age, and BMI have been proposed as factors that influence energy intake and alter gastric emptying [ 110 , 111 , 112 ]. Gender is the major contributor to differences in gastric motor functions, with gastric emptying being around 15% slower in females and influencing the energy intake in controlled interventions [ 64 , 111 ].…”
Section: Gastric Sensory and Motor Functions And Food Intakementioning
confidence: 99%
“…Basic features such as gender, age, and BMI have been proposed as factors that influence energy intake and alter gastric emptying [ 110 , 111 , 112 ]. Gender is the major contributor to differences in gastric motor functions, with gastric emptying being around 15% slower in females and influencing the energy intake in controlled interventions [ 64 , 111 ].…”
Section: Gastric Sensory and Motor Functions And Food Intakementioning
confidence: 99%
“…We have reported that healthy, non-obese, young men, but not women, experience significant suppression of hunger ratings and ad libitum food intake three hours after 30 gm and 70 gm whey protein drinks [ 42 , 44 , 47 ]. In contrast, and consistent with their reduced responses to intra-duodenal whey, healthy, non-obese men and women over 65 years experience little reduction in hunger and no suppression of ad libitum food intake three hours after either 30 gm or 70 gm whey drinks [ 44 , 47 , 48 , 49 , 50 ].…”
Section: Gastrointestinal Responses To Protein Ingestion: Effects Of Agingmentioning
confidence: 99%
“…The oral ingestion of nutrients, irrespective of their type, slows gastric emptying. Gastric emptying of non-nutrient drinks is slightly slower in older than in young adults [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Whey protein drinks in doses of 30–70 gm slow gastric emptying in a dose-responsive manner [ 42 , 44 , 50 ], and probably slow it more in older than in young adults; the stomachs of healthy older men emptied whey into the duodenum at approximately 0.8 kcal/min compared with 1.0 kcal for young adult men ( p < 0.05) in one study [ 44 ].…”
Section: Gastrointestinal Responses To Protein Ingestion: Effects Of Agingmentioning
confidence: 99%
See 2 more Smart Citations